Gamified virtual exercise as a strategic management tool to foster inclusivity in women’s wellbeing and sports tourism - Faridniya, Hossein; George, Reena (Frontiers in Virtual Reality, 2025)
IntroductionThis study aimed to evaluate the effectiveness of gamified virtual reality (VR) exercise as a strategic intervention to enhance body image perception and social interaction among overweight women with clinically diagnosed social anxiety, and further to explore the potential of VR-based physical activity in promoting inclusivity and well-being within the context of sports tourism and experiential wellness.MethodsA quasi-experimental pretest–posttest design was employed with 128 women aged 20–40 who were categorized as having class I or II obesity (BMI 30–40). Participants were randomly assigned to either a 12‐session gamified VR exercise program delivered across 4 weeks (three sessions per week) or a standard gym-based exercise group of equal duration and intensity. Validated self-report instruments were administered before and after the intervention, and analysis of covariance (ANCOVA) was conducted to examine between‐group differences while controlling for baseline scores.ResultsResults indicated that the VR intervention group showed significantly greater improvements in body image flexibility (F = 51.30, p < 0.001, η2 = 0.286) and social interaction (F = 46.24, p < 0.001, η2 = 0.266) compared with the control group, along with a moderate reduction in BMI.DiscussionThese findings suggest that gamified VR-based exercise is an effective and engaging approach to improving psychological well‐being and promoting inclusive participation among women who face social and emotional barriers to physical activity, while also holding promise as a strategic asset for fostering engagement in sports tourism and broader community wellness initiatives.